A Systematic Review: Family Support Integrated with Diabetes Self-Management among Uncontrolled Type II Diabetes Mellitus Patients - Pamungkas, Rian; Chamroonsawasdi, Kanittha; Vatanasomboon, Paranee (Behavioral sciences, 2017)
The rate of type-2 diabetes mellitus (T2D) is dramatically increasing worldwide. Continuing diabetes mellitus (DM) care needs effective self-management education and support for both patients and family members. This study aimed to review and describe the impacts of diabetes mellitus self-management education (DSME) that involve family members on patient outcomes related to patient health behaviors and perceived self-efficacy on self-management such as medication adherence, blood glucose monitoring, diet and exercise changes, health outcomes including psychological well-being and self-efficacy, and physiological markers including body mass index, level of blood pressure, cholesterol level and glycemic control. Three databases, PubMed, CINAHL, and Scopus were reviewed for relevant articles. The search terms were “type 2 diabetes,” “self-management,” “diabetes self-management education (DSME),” “family support,” “social support,” and “uncontrolled glycaemia.” Joanna Briggs Institute (JBI) guidelines were used to determine which studies to include in the review. Details of the family support components of DSME intervention and the impacts of these interventions had on improving the health outcomes patients with uncontrolled glycaemia patients. A total of 22 intervention studies were identified. These studies involved different DSME strategies, different components of family support provided, and different health outcomes to be measured among T2D patients. Overall, family support had a positive impact on healthy diet, increased perceived support, higher self-efficacy, improved psychological well-being and better glycemic control. This systematic review found evidence that DSME with family support improved self-management behaviors and health outcomes among uncontrolled glycaemia T2D patients. The findings suggest DSME models that include family engagement can be a useful direction for improving diabetes care.